Environment Attitude Of The People And Stakeholders Towards Urban Biodiversity In Kuala Lumpur, Malaysia - Baharuddin , Zainul Mukrim (Journal of Architecture, Planning and Construction Management, 2020)
Urban biodiversity and wildlife management have been accepted as important ecological components of the urban environment. The world population is increasing very rapidly, overwhelming all efforts in urban wildlife protection and management. The urban population is growing at a much faster rate than the population as a whole. In 2009, there were 3.42 billion people living in towns and cities and this is predicted to increase to 6.3 billion by 2050. This poses major challenges to those responsible for the provision of green spaces and for preserving the biodiversity of urban areas. It is reasonably clear that biodiversity protection and management are deficient in almost all cities in developing countries. The deficiencies are not the same in all cities, but they generally relate to the perceptions of citizens and stakeholders. Urban green space and biodiversity are crucial in achieving sustainable cities because they involve social, economic and environmental issues and, if managed properly, result in ecological benefits for the cities’ inhabitants. However, in Malaysia, landscape and urban green space have received little attention in land use planning. In Malaysia, very limited research has been undertaken to gain an understanding of people’s preferences towards biodiversity such as wildlife. Furthermore, there is limited understanding of people’s preferences on urban biodiversity either in the single species approach or in their general preferences. Kuala Lumpur aims to promote and improve the quality of its living environment and to develop a sustainable approach for the development of urban green space. Thus, it is important to understand the attitude of people towards local urban parks and biodiversity especially wildlife and how it relates to the planning and development of green open spaces.